Effects of Impacted Lower Third Molar Extraction on Periodontal Tissue of the Adjacent Second Molar - Zhang Y; Chen X; Zhou Z; Hao Y; Li H; Cheng Y; Ren X; Wang X (Dove Medical Press, 2021)
Yuan Zhang,1,2,* Xiaohang Chen,1,2,* Zilan Zhou,1,2 Yujia Hao,1,2 Huifei Li,1,2 Yongfeng Cheng,1,2 Xiuyun Ren,1,2 Xing Wang1,2 1Shanxi Medical University School and Hospital of Stomatology, Taiyuan, 030001, People’s Republic of China; 2Shanxi Province Key Laboratory of Oral Diseases Prevention and New Materials, Taiyuan, 030001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xing Wang; Xiuyun RenShanxi Medical University School and Hospital of Stomatology, Taiyuan, 030001, People’s Republic of ChinaEmail tt1984621@163.com; rxy611@163.comAbstract: The extraction of impacted lower third molars (ILTM) is one of the most common procedures in oral-maxillofacial surgery. Being adjacent to lower second molars, most impacted lower third molars often lead to distal periodontal defects of adjacent second molars. Several symptoms may occur after extraction, such as periodontal pocket formation, loss of attachment, alveolar bone loss and even looseness of second molar resulting in extraction. The distal periodontal defects of second molars are affected by many factors, including periodontal conditions, age, impacted type of third molars, and intraoperative operations. At present, several studies have suggested that dentists can reduce the risk of periodontal defects of the second molar after ILTM extraction through preoperative evaluation, reasonable selection of flap design, extraction instruments and suture type, and necessary postoperative interventions. This review summarizes the research progress on the influence factors, interventions methods and some limitations of distal periodontal defects of adjacent second molar after extraction of impacted mandibular third molars, with the aim of opening up future directions for studying effects of ILTM extraction on periodontal tissue of the adjacent second molar.Keywords: impacted lower third molar, periodontal defect, alveolar bone defect, second molar, teeth extraction